2018
DOI: 10.1161/jaha.118.009237
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Treatments of Patients Enrolled in the CHAMP‐HF Registry Compared With Patients Enrolled in the PARADIGM‐HF Trial

Abstract: BackgroundThe US Food and Drug Administration approved sacubitril/valsartan for patients with chronic heart failure (HF) with reduced ejection fraction in 2015 on the basis of the results of the PARADIGM‐HF (Prospective Comparison of ARNI [Angiotensin Receptor Neprilysin Inhibitor] With ACEI [Angiotensin‐Converting Enzyme Inhibitor] to Determine Impact on Global Mortality and Morbidity in Heart Failure) trial. There are limited data assessing the generalizability of PARADIGM‐HF trial participants to a broader … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 12 publications
1
17
1
1
Order By: Relevance
“…The proportion of patients in this study with HF of NYHA class III is also higher than observed in other real-world studies of sac/val. 13,17 The differences in HF severity observed between the current study and other real-world studies may be partly explained by the low number of patients in the current cohort with a recorded NYHA class. Nevertheless, the overall higher severity of HF seen in these populations compared with PARADIGM-HF may partly explain the overall lower dosing of sac/val at initiation in clinical practice.…”
Section: Patient Demographics and Clinical Characteristicsmentioning
confidence: 73%
See 1 more Smart Citation
“…The proportion of patients in this study with HF of NYHA class III is also higher than observed in other real-world studies of sac/val. 13,17 The differences in HF severity observed between the current study and other real-world studies may be partly explained by the low number of patients in the current cohort with a recorded NYHA class. Nevertheless, the overall higher severity of HF seen in these populations compared with PARADIGM-HF may partly explain the overall lower dosing of sac/val at initiation in clinical practice.…”
Section: Patient Demographics and Clinical Characteristicsmentioning
confidence: 73%
“…Among patients who were prescribed sac/val 24/26 mg b.i. d. at index, there was no difference in mean (SD) SBP between those who were stably up-titrated and those who were not titrated [123 (17) mmHg vs. 122 (20) mmHg, respectively; Table 2] or in the proportion of patients with low SBP (<100 mmHg, 8% in both groups). Moreover, there were no patients with a recorded low SBP (<100 mmHg) among those Similar mean (SD) K + levels were observed in patients who were stably up-titrated and those who were not titrated regardless of whether they had a starting dose of Among patients who received 24/26 mg b.i.d.…”
Section: Patient Demographics and Clinical Characteristicsmentioning
confidence: 98%
“…13,14,28 Looking at novel HFrEF therapies, only 11% of patients in DAPA-HF were treated with the angiotensin receptor-neprilysin inhibitor combination, sacubitril/valsartan, a finding consistent with the 13% receiving this therapy in the recent CHAMP-HF registry mentioned above. 13,14,29 However, the percentage treated with sacubitril/valsartan varied widely in DAPA-HF, from 32% in North America and 25% in Western Europe to 7% or less in other regions, perhaps reflecting different economic circumstances and health service provision. Ivabradine was also little used in recent trials and registries.…”
Section: Discussionmentioning
confidence: 99%
“…There are considerable regional differences in patient characteristics reported in global clinical registries and trials . In the following sections, we focused on studies published after 2010 to reduce time‐lag and increase comparability between studies and registries ( Tables ) . In the PARADIGM‐HF trial, patients from AP were almost a decade younger compared to patients from NA and WE .…”
Section: Regional Differences In Heart Failurementioning
confidence: 99%
“…19 In the following sections, we focused on studies published after 2010 to reduce time-lag and increase comparability between studies and registries ( Tables 1-3). 8,11,13,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] In the PARADIGM-HF trial, patients from AP were almost a decade younger compared to patients from NA and WE. 8 This is in line with recent reports of the ASIAN-HF registry and signifies a potentially shifting burden of HF from NA, WE and EE to the AP region.…”
Section: Overall Clinical Characteristicsmentioning
confidence: 99%